Russia's internal Abroad: The North Caucasus as an Emergency Zone at the Edge of Europe - Uwe Halbach (Stiftung Wissenschaft und Politik (SWP), 2010)
The North Caucasus with its seven Russian Federation republics has witnessed an alarming increase in the number of acts of terrorism in the region as well as military conflicts between state security bodies and armed resistance groups. This development extends beyond the borders of the former war zone in Chechnya, which has long dominated reporting on the North Caucasus. The neighbouring republics of Dagestan and Ingushetia surpassed Chechnya in the last two years in terms of the number of "acts of violence". Republics in the region's central and western reaches, however, have also seen increases in these figures. In his address before the Federal Assembly in 2009, President Medvedev pointed to the North Caucasus as constituting Russia's preeminent domestic problem. In 2010, he introduced administrative reform by creating a separate federal district for the region. Russian politicians emphasise socio-economic and political causes for the violence and have increasingly stressed the importance of reforms rather than solely relying on "clampdowns". Will such new approaches in Russia's Caucasus strategy stand up against the security policy challenges coming from the region? For the time being, new incidents of violence are being recorded every week. A European "Partnership for Modernisation" with Russia cannot ignore the disastrous security situation in Russia's "internal abroad" in the North Caucasus. The region represents an exposed emergency zone on the edge of Europe
Keywords: 320